Serum calcium and serum phosphate levels in transfusion dependent beta thalassemia - Sultana, Mst Ariza; Akhter, Qazi Shamima (Journal of Bangladesh Society of Physiologist, 2018)
Background: Patients with transfusion dependent beta thalassemia with severeanemia require regular blood transfusion to improve quality of life. This can lead to iron overload which might cause various complications including hypocalcaemia. Objective: To estimate the serum calcium and phosphate levels in transfusion dependent beta thalassemia patients. Methods: This cross-sectional study was conducted in the Department of Physiology, Dhaka Medical College, Dhaka from July 2016 to June 2017. After fulfilling the ethical aspect, a total number of 60 subjects were selected with the age ranging from 5 to 25 years. Among them, 40 transfusion dependent beta thalassemia patients were selected as the study group and 20 age and sex matched apparently healthy individuals were considered as control group for comparison. The study population were selected from Thalassemia foundation hospital, Dhaka. Theserum calcium and phosphate levels were estimated by autoanalyzer.. For statistical analysis, unpaired Student’s‘t’ test, Chi-square test were performed as applicable. Results: In this study, serum calcium level were significantly (p < 0.001) lower and serum phosphate level were significantly (p < 0.001) higher in transfusion dependent beta thalassemia patients as compared to healthy controls. In addition, 67.5% thalassemia patients had hypocalcemia (calcium level < 8.5 mg/dl) and 85% of thalassemia patients had hyperphosphatemia(phosphate level > 4.7mg/dl). Conclusions: This study concludes transfusion dependent beta thalassemiapatients have low calcium level and high serum phosphate level which should be monitored to avoid complications related to hypocalcaemia and hyperphosphatemia. J Bangladesh Soc Physiol. 2018, December; 13(2): 54-58